Rooting the nature of innovation - Al-Musawi, Hawraa Ibrahim Jasim; Hussein, Wasan Salih (Al-Adab Journal, 2021)
This research establish for the essence of innovation in Arabic criticism as the innovation is considered the highest grade in artistic especially in Arabic poetry and it becomes a criticism standard in introducing the poets .This research shows its concept , terms and words .It is divided into four main points .In the first point it studies the dictionary innovation words .In the second point it discusses the circulated description words .In the third point it discusses the rhythm innovation words ,The fourth point studies other words ,This research reaches to more than (thirty five) words that were mentioned in the critics speech expressing the innovation as well as other words take the favored meaning and others.